A reduction in training volume and intensity for 21 days does not impair performance in cyclists. Issue 6 (1st December 2001) - Rietjens, G J W M; Keizer, H A; Kuipers, H; Saris, W H M
Abstract : Objectives —( a ) To investigate the effects of reduced training on physical condition and performance in well trained cyclists; ( b ) to study whether an intermittent exercise programme would maintain physiological training adaptations more effectively than a continuous exercise programme during a period of reduced training. Methods —Twelve male cyclists participated in a 21 day training programme and were divided into two training groups. One group (age 25.3 (7) years; weight 73.3 (5.7) kg; Vo 2 max 58.6 (4.5) ml/kg/min; means (SD)) underwent a continuous endurance exercise training programme (CT) whereas the second group (age 22.8 (3.5) years; weight 74.1 (7.0) kg; Vo 2 max 59.7 (6.7) ml/kg/min) followed an intermittent endurance exercise training programme (IT). During this reduced training period, both groups trained for two hours a day, three days a week. Results —Neither group showed changes in maximal workload (Wmax ) (4.6 (0.5) v 4.8 (0.5) W/kg and 4.6 (0.5) v 4.7 (0.6) W/kg for the CT and IT group respectively) and Vo 2 max (58.6 (4.5) v 60.1 (5.8) ml/kg/min and 59.7 (6.7) v 58.8 (7.5) ml/kg/min for the CT and IT group respectively). During the submaximal steady state exercise test, substrate use and heart rate remained unchanged after reduced training. Conclusions —These results indicate that well trained cyclists who reduce training intensity and volume for 21 days can maintain physiological adaptations, as measured during submaximal and maximal exercise. An intermittent training regimen has no advantage over a continuous training regimen during a detraining period.